REWARD AND EMPLOYEE PRODUCTIVITY IN SELECTED LARGEPRIVATE ORGANIZATIONS IN THE SOUTH-EAST, NIGERIA - M. N, OKEKE,; A.N, ONUORAH,; J.C , OBOREH,; ECHO, OJAN (IJRDO - Journal of Business Management, 2019)
The study examined the effect of reward on employee productivity in selected large private organizations in South-East, Nigeria. As a descriptive survey design, a sample of 336 respondents was determined from the population of 2081 senior employees of Serbmilla Industries, Onitsha, Nigeria Breweries PLC Ama-Enugu and Nigeria Bottling Company, Irrete, Owerri, Imo-State. Units of Observation (Sampling points) were selected through the method of systematic sampling. Out of 336 copies of the questionnaire distributed, 321 were completed and returned thus showing a response rate of 95.5 percent which was considered very adequate. Through the application of Chi-Square (χ2) inferential statistics, pearson product moment correlation coefficient and t-test for significance of ‘r’, as the tools of analysis, the result showed that task autonomy significantly affects employee productivity. Also, the analysis revealed that task involvement influences job satisfaction and productivity. It was equally found from the analysis of data that tasks significance and employee empowerment enhance employee performance in the organization. It was concluded that empowered organizational climate would help to create a pool of committed and self-motivated individuals with visions, creativity, innovation and technical powers to convert the threat of change into opportunities for business growth and development. It was recommended among others that management should try to create an environment conducive for maximum utilization of employees’ skills, competencies creativity and talents for the benefit of all stakeholders in the organization.